2009
DOI: 10.1371/journal.pone.0004260
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Extrusion by NCX Is Compromised in Olfactory Sensory Neurons of OMP−/− Mice

Abstract: BackgroundThe role of olfactory marker protein (OMP), a hallmark of mature olfactory sensory neurons (OSNs), has been poorly understood since its discovery. The electrophysiological and behavioral phenotypes of OMP knockout mice indicated that OMP influences olfactory signal transduction. However, the mechanism by which this occurs remained unknown.Principal FindingsWe used intact olfactory epithelium obtained from WT and OMP−/− mice to monitor the Ca2+ dynamics induced by the activation of cyclic nucleotide-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 85 publications
0
61
0
Order By: Relevance
“…In the Biacore setting, CaM was immobilized via amino coupling on a CM5 chip and Peptide X was applied on the sensor surface [14]. The binding affinity was estimated to be around ~20 nM confirming the QCM-D data.…”
Section: + /Cam Binding To Various Peptidesmentioning
confidence: 65%
See 1 more Smart Citation
“…In the Biacore setting, CaM was immobilized via amino coupling on a CM5 chip and Peptide X was applied on the sensor surface [14]. The binding affinity was estimated to be around ~20 nM confirming the QCM-D data.…”
Section: + /Cam Binding To Various Peptidesmentioning
confidence: 65%
“…Among them, XIP (exchanger Inhibitory Peptide) region of sodium calcium exchanger (NCX) is a well-known peptide, which we will call peptide X for simplicity. NCX is known to bind to Ca 2+ /CaM [14] to regulate its ion transport functionality and the peptide X inhibits its own NCX activity when applied in the cytosol [15]. Studying interaction between CaM and peptides that are involved in the single signal transduction cascade would serve as an example to demonstrate versatility of CaM configuration in target binding.…”
Section: Introductionmentioning
confidence: 99%
“…In VSNs, receptor activation by a variety of chemosensory ligands generates a transient elevation of intracellular Ca 2ϩ that begins in the VSN microvilli and then propagates toward the cell soma Cinelli et al, 2002;Spehr et al, 2002;Leinders-Zufall et al, 2004;Chamero et al, 2007;He et al, 2008). Such Ca 2ϩ transients are known to depend primarily on Ca 2ϩ entry through Ca 2ϩ -permeable, TRPC2-dependent cation channels (Lucas et al, 2003;Zufall et al, 2005), although the possibility that a secondary Ca 2ϩ release from intracellular stores, as in OSNs Kwon et al, 2009), contributes to Ca 2ϩ signaling remains to be tested. The present study identifies native TRPC2-dependent channels as a target for negative feedback regulation by elevated intracellular Ca 2ϩ .…”
Section: Modulation Of Diacylglycerol-sensitive Cation Channels By Camentioning
confidence: 99%
“…We speculated that OMP modulated Ca 2+ -mediated PKC/ MAPK signaling, which is the main pathway responsible for TRH-induced PRL expression. Previous studies have shown that OMP modulates Ca 2+ extrusion from olfactory sensory neurons by directly interacting with brainexpressed X-linked 1 (Bex1) proteins, which can also bind to the Ca 2+ -dependent modulator, calmodulin (CaM) 8,11,13,39,40 . The OMP-Bex1-CaM interaction can explain the desensitization to TRH stimulation that is observed in the absence of OMP.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory marker protein (OMP) is a small, cytoplasmic protein that is abundantly and almost exclusively expressed in vertebrate olfactory neurons [5][6][7][8] . Previous studies have shown that OMP modulates olfactory signal transduction in part by participating in Ca 2+ clearance [8][9][10][11][12][13] . Microarray and RNA sequencing analyses have revealed that OMP is also expressed in non-olfactory tissues, often with odorant receptors (ORs), which constitute a major class of G protein-coupled receptor (GPCR) 14,15 .…”
Section: Introductionmentioning
confidence: 99%